PEMBELAJARAN TARI MELINTING DI SMA NEGERI 1 METRO - Anastasia Asih Kartikawaty; Susi Wendhaningsih; Muhammad Fuad (Jurnal Seni dan Pembelajaran, 2013)
The problems in this research are how the process and the learning result of melinting dance in the second semester students 2012-2013 at SMAN 1 Metro. The purpose of this research is to describe the activities of the students in the learning process of the Melinting dance and the learning result after it. This research used descriptive qualitative approach research. The data resources of this research are dancing teacher and 26 students. The data will be obtained by observation method, interview, and documentation. From the result of this research, it showed that the learning process was involved student learning activities is visual activities, listening activities, motoric activities, and emotional activities. Generally, the student’s learning result have an enough criterion with the best grade criterion was (12%) 3 students, in a good criterion was (38%) 10 students, and enough criterion was (50%) 13 students.Permasalahan dalam penelitian ini adalah bagaimana proses dan hasil pembelajaran tari melinting pada siswa angkatan 2012-2013 semester 2 IPA 5 di SMA Negeri 1 Metro. Tujuan dalam penelitian ini adalah untuk mendeskripsikan aktivitas siswa dalam pembelajaran tari melinting dan hasil belajar siswa setelah proses pembelajaran tari melinting. Penelitian ini menggunakan pendekatan penelitian deskriptif kualitatif. Sumber data dalam penelitian adalah guru seni tari, dan 26 siswa. Teknik pengumpulan data adalah dengan menggunakan metode observasi, wawancara, dan dokumentasi. Dari hasil penelitian terlihat bahwa proses pembelajaran terkait aktivitas belajar siswa yang diamati adalah visual activities,listening activities, motor activities, emotional activities. Pada hasil belajar siswa secara umum memperoleh nilai cukup dengan kriteria baik sekali (12%) sebanyak 3 orang siswa, kriteria nilai baik (38%) sebanyak 10 orang siswa, dan kriteria nilai yang cukup baik (50%) adalah sebanyak 13 orang siswa.Kata kunci: pembelajaran, SMAN 1 metro, tari melinting,